FusionAI, a DNA-sequence-based deep learning protocol reduces the false positives of human fusion gene prediction - Pora Kim; Hua Tan; Jiajia Liu; Himansu Kumar; Xiaobo Zhou (STAR Protocols, 2022)
Summary: Even though there were many tool developments of fusion gene prediction from NGS data, too many false positives are still an issue. Wise use of the genomic features around the fusion gene breakpoints will be helpful to identify reliable fusion genes efficiently. For this aim, we developed FusionAI, a deep learning pipeline predicting human fusion gene breakpoints from DNA sequence. FusionAI is freely available via https://compbio.uth.edu/FusionGDB2/FusionAI.For complete details on the use and execution of this protocol, please refer to Kim et al. (2021b).